WORK EXPERIENCE ANALYSIS OF INTERNATIONAL PROFESSIONAL SPORTS ACADEMIES FOR EFFECTIVE IMPLEMENTATION OF CREATION AND DEVELOPMENT SPORTS ACADEMIES PROJECTS IN RUSSIA - I. Kolesov (Вестник университета, 2018)
The article provides an overview of youth academies organization practice in football and hockey clubs in Europe. It involves four key directions which permit to enhance operation efficiency of sports clubs: ideology and goals; infrastructure; organization; player’s training and interaction with parents. Report on youth academies in Europe by European club association is used as a source of statistics. The international practice study can help sport managers to develop youth sport academies in Russia.